PROGRAM PENDAMPINGAN BELAJAR DENGAN MODEL REFLEKTIF UNTUK MENINGKATKAN KETERAMPILAN METAKOGNITIF SISWA SMA - Tuty Alawiyah (Journal of Innovative Counseling : Theory, Practice, and Research, 2017)
This study aims to design and examine the effectiveness of learning assistance program using learning reflective model to improve cognitive skills of upper-secondary students in girls dormitory of Darul Hikam International School Academic Year 2016/2017. This study based on the profile of students’metacognitive skills, the low metacognitive skills of students, and the need for program to improve the students’metacognitive skills. This study uses a quasi experimental method and pretest-posttest control group design. Based on the pre-test given to 48 upper-secondary students, there are 16 students whose metacognitive skills is in low category and the rest is in high and middle category. The 16 student’s then are devided into two groups, 8 students as the control group and 8 students as experimental group. The research finding shows there is metacognitive skills improvement of experimental group after following the leaning assistance program using reflective learning model. Therefore, it can be concluded that the learning assistance program using reflective learning model proven effective to improve students’ metacognitive skills.